PENGARUH PERSEDIAAN DAN VOLUME PENJUALAN TERHADAP LABA BERSIH PADA INDOMARET ISKANDAR MUDA BABUSALAM - Rudi Aris Munandar; Ardi Hirmansah; Bahrul Ilmi (EKSPOLHUM, 2026)
This study aims to analyze the effect of inventory and sales volume on net profit at PT Indomarco Prismatama (Indomaret Iskandar Muda Babusalam) during the period January 2020–December 2024. The research employed a quantitative descriptive approach using secondary data from monthly financial reports over five years (60 observations). Data were analyzed using SPSS through descriptive statistics, classical assumption tests, multiple linear regression, t-test, F-test, and coefficient of determination. The results indicate that inventory partially has a positive and significant effect on net profit. Sales volume also partially shows a positive and significant effect on net profit. Simultaneously, inventory and sales volume significantly influence net profit. The Adjusted R² value of 0.453 implies that 45.3% of the variation in net profit can be explained by the independent variables, while 54.7% is influenced by other factors such as cash flow and capital. These findings highlight the importance of effective inventory management and increased sales volume in improving retail company profitability.